2019
DOI: 10.1088/1755-1315/357/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Flash flood area mapping using sentinel-1 SAR data: a case study of eight upazilas in Sunamganj district, Bangladesh

Abstract: Extraction of information from Remote sensing satellites is significant and effective tools for hazard activities such as flooding. essentially, if the field was under disaster conditions it will be so difficult to do surveying in that region. flash floods are sudden natural disaster events, which impact an extensive variety of ecological elements and applications associated with natural resources, agriculture, human activities and natural phenomena and economies. The utilization of SAR information gives much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Experience and learning are two notable attributes of community resilience to flooding in Bangladesh (Haque and Zaman, 1993). Recent studies on flash flood experience in Bangladesh's wetlands have revealed increased vulnerability due to unprecedented magnitude of runoffs and river discharges, and a shift in timing of pre-monsoon and monsoon rainfall (Aldhshan et al, 2019;Kamal et al, 2018;Rahman et al, 2020). While numerous studies have confirmed that flood perceptions, social relationships, emotional attachment, living with floods and livelihood stresses are the key stepping-stones for adaptive learning and flood-related knowledge to foster resilience (Choudhury and Haque, 2016;Cook, 2010;Rahman et al, 2018), experiential learning alone would not suffice to deal with emerging flood risks.…”
Section: Social Learning From Floods In Bangladeshmentioning
confidence: 99%
See 3 more Smart Citations
“…Experience and learning are two notable attributes of community resilience to flooding in Bangladesh (Haque and Zaman, 1993). Recent studies on flash flood experience in Bangladesh's wetlands have revealed increased vulnerability due to unprecedented magnitude of runoffs and river discharges, and a shift in timing of pre-monsoon and monsoon rainfall (Aldhshan et al, 2019;Kamal et al, 2018;Rahman et al, 2020). While numerous studies have confirmed that flood perceptions, social relationships, emotional attachment, living with floods and livelihood stresses are the key stepping-stones for adaptive learning and flood-related knowledge to foster resilience (Choudhury and Haque, 2016;Cook, 2010;Rahman et al, 2018), experiential learning alone would not suffice to deal with emerging flood risks.…”
Section: Social Learning From Floods In Bangladeshmentioning
confidence: 99%
“…Experience and learning are two notable attributes of community resilience to flooding in Bangladesh (Haque and Zaman, 1993). Recent studies on flash flood experience in Bangladesh's wetlands have revealed increased vulnerability due to unprecedented magnitude of runoffs and river discharges, and a shift in timing of pre-monsoon and monsoon rainfall (Aldhshan et al. , 2019; Kamal et al.…”
Section: Conceptual Considerations – a Social Learning From Disasters...mentioning
confidence: 99%
See 2 more Smart Citations
“…To vividly depict a community's ICT utilization, it is necessary to understand the people's socio-economic characteristics, their location, ICT coverage, and their responses Flash floods occur in this area mainly due to heavy rainfall from the very steep uplands in the Meghalaya Hills [24]. The Meghalaya Hills on the Indian side of the border are among the world regions that receive the maximum annual rainfall (12,000 mm).…”
Section: Studied Communitiesmentioning
confidence: 99%